Blood pressure screening programs: a case report - Ana Carolina Queiroz Godoy Daniel; Eugenia Velludo Veiga; Sarah da Silva Candido; Cynthia Kallás Bachur; José Luiz Tatagiba Lamas; Silvana Maria Coelho Leite Fava (Universidade Federal de Santa Maria, 2021)
Objective: To report on the experience of developing and implementing Blood Pressure Screening Programs carried out in Brazil from 2015 to 2018. Method: A case report conducted in five Brazilian cities, covering the following stages: Elaboration, cooperation, recruitment, development, planning, training, dissemination, execution, and analysis. Results: Partnerships with public and private institutions were established for the implementation of the screening. Students and healthcare providers were trained to measure blood pressure, fill out the data collection instrument, and orient the participants. A schedule was prepared to address the locations, dates, times, human resources, and supplies needed to carry out the activities. The indicators prevalence, knowledge, treatment, and hypertension management comprised the descriptive analysis of the collected data. Conclusion: The methodological procedures presented in this study are capable of supporting the development and implementation of systematized blood pressure screening programs in Brazil.